Evaluación del almidón de yuca (Manihot esculenta) y mucílago de moyuyo (Cordia lutea) en la elaboración de láminas bioplásticas - Carrillo Pachay, Marco Steve (2024)
Plastic abuse and its slow degradation are global environmental concerns, driven by its rampant production and consumption. This research focused on evaluating cassava starch and moyuyo mucilage could influence the production of bioplastic sheets. For this, a completely randomized design was applied with six treatments that combine different amounts of cassava starch (25, 30 and 35 g) and moyuyo mucilage (22 and 28 ml). The population projection of the Bolívar canton for the year 2035 is 48,219 inhabitants, with an annual growth of 1.1%, where the most generated polymer was Polyethylene Terephthalate (PET) with 34.8% and the lowest was Low Polyethylene. density (LDPE) with 6.5%. Polypropylene exhibited the highest density among the plastics analyzed with 0.213 g/cm3. In addition, the highest generation per capita is observed in Polyethylene Terephthalate (PET) 0.0001275 kg/Hab/day, and the lowest generation was Low Polyethylene. density (LDPE) 0.0000240 kg/Hab/day. The physical and mechanical properties of the bioplastic sheets were measured, with T3 being the one that demonstrated the best characteristics in terms of thickness (0.15 mm), elongation (28.13%), highest tensile strength (36.46 MPa) and lowest T1 (24.23 MPa) complying with the established range, while in humidity T4 presented the best percentage of (22.17%) complying with the established. All treatments showed biodegradability within a period of 30 days. Treatment T1 presented greater mass loss (64.66%), while treatment T4 had less (50.51%). Finally, the economic study for the production of bioplastic sheets measuring 20x15 cm was based on treatment T3, which has a total production cost of $0.72 and a sales price of $0.86.